‘The teachers do not see us.’ The challenges of teacher education in rural areas - Johanson, Lisbeth Bergum; Karlsen, Silje Solheim (University of Aberdeen, 2021)
The northernmost region of Norway has difficulties in recruiting qualified teachers, in 2019 9.5 % of the teachers in Finnmark were unskilled. To ensure education for people who, for various reasons, are unable to move to education centres to study, UiT the Arctic University of Norway offers a flexible teacher education model from campus Alta. This is a model which alternates between teaching on campus, home studies and online supported teaching in different nodes/localities. In this article we present a case study addressing some of the challenges with flexible teacher education connected to structure, technology and digital didactics. Through interviews and observations we have collected data from both teachers and students, which raises questions concerning the organisational forms of teacher education. ICT-support must be ensured by the educational institution and not be entrusted to the teachers. The opportunities for gaining relevant competence must be facilitated. Furthermore, a flexible education model demands adapted pedagogical and didactical thinking. content Full content in PDF